Palatal vault morphometric analysis of the effects of two early orthodontic treatments in anterior open bite growing subjects: a controlled clinical study - Paoloni, Valeria; Fusaroli, Dimitri; Marino, Ludovica; Mucedero, Manuela; Cozza, Paola (BMC oral health, 2021)
Background The purpose of this study was to evaluate the palatal morphological changes in Anterior Open Bite (AOB) pre-pubertal subjects treated with Rapid Maxillary Expansion and Bite-Block (RME/BB) or Quad Helix with crib (QH/C) when compared with a Control Group (CG) by using Geometric Morphometric Analysis (GMM). Methods AOB group (AOBG) included 30 subjects (20 females, 10 males, mean age 8.1 [+ or -] 0.8ys) with dentoskeletal AOB. AOBG was divided in two subgroups according to the treatment strategy: RME/BB group (RME/BBg) included 15 subjects (10 females, 5 males, QH/C group (QH/Cg) comprised 15 subjects (10 females, 5 males). The two subgroups were compared with a CG of 15 subjects (10 females, 5 males) matched for sex, age, vertical pattern, and observation period. Digital upper dental casts were collected before treatment (T1) and at the end of the active treatment (T2). Landmarks and semilandmarks were digitized on dental casts and GMM was applied. Procrustes analysis and principal component analysis (PCA) were performed. Results At T2, RME/BBg when compared with QH/Cg evidenced no statistically significant differences. Instead, RME/BBg showed an increased maxillary transverse dimension and a decreased palatal depth when compared with CG. The comparison QH/Cg vs. CG demonstrated a slight transversal maxillary expansion. Conclusions RME/BBg showed significant changes in the transversal and vertical dimensions with a clear maxillary expansion and a decrease of the palatal depth when compared with QH/Cg and CG. QH/Cg showed a significant slight maxillary expansion and no variation in vertical and sagittal planes when compared with CG. Keywords: Anterior open bite, Early treatment, RME, Bite-Block, Quad Helix with crib, Palatal vault, GMM